2023
DOI: 10.1177/07340168231160862
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Criminogenic Risk Factors Among United States Military Veterans: An Updated Literature Review

Abstract: Justice-involved veterans (JIVs) are a high-priority subgroup within the U.S. judicial system. In recent years, empirical research into the characteristics, needs, and outcomes of this veteran subgroup has developed rapidly. To allow research to better inform efforts to support JIVs, a systematic review was completed to organize existing literature on criminogenic risk within this population through the lens of the Risk-Need-Responsivity Model. Of the eight risk factors theorized by the Risk-Need-Responsivity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 97 publications
0
5
0
Order By: Relevance
“…Data collected prior to veteran participation provide insight into the needs of JIVs seeking outpatient care within the VHA. To date, research on criminogenic risk and commonly co-occurring difficulties among treatment-seeking JIVs has been somewhat limited (Edwards et al, 2023). As a result, efforts to support JIVs have been largely unable to tailor interventions to the unique needs and motivations of JIVs (Blonigen et al, 2017), potentially contributing to observed difficulties in participant engagement (Blonigen et al, 2021(Blonigen et al, , 2022.…”
Section: Participant Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Data collected prior to veteran participation provide insight into the needs of JIVs seeking outpatient care within the VHA. To date, research on criminogenic risk and commonly co-occurring difficulties among treatment-seeking JIVs has been somewhat limited (Edwards et al, 2023). As a result, efforts to support JIVs have been largely unable to tailor interventions to the unique needs and motivations of JIVs (Blonigen et al, 2017), potentially contributing to observed difficulties in participant engagement (Blonigen et al, 2021(Blonigen et al, , 2022.…”
Section: Participant Characterizationmentioning
confidence: 99%
“…Correction to Edwards et al (2023) In the article "Dialectical Behavior Therapy for Justice-Involved Veterans: Changes in Treatment Targets in a Small, Pre-Postdesign Clinical Trial," by Emily R. Edwards, Gabriella Epshteyn, Shayne Snyder, Daniel Gorman, Brettland Coolidge, Eddie Marcano, Jack Tsai, and Marianne Goodman (Psychological Services, advance online publication, April 13, 2023, https://doi.org/10.1037/ser0000766), the title was incorrect and should have been "Dialectical Behavior Therapy for Justice-Involved Veterans: Changes in Treatment Targets in a Small, Pre-Post Design Clinical Trial." This error did not impact the results or conclusions.…”
mentioning
confidence: 99%
“…Results from population studies have also demonstrated that military members are more prone to lifetime arrests relative to other demographics (Snowden et al, 2017) and research on the relative risk of imprisonment between veterans and nonveterans has indicated that they are significantly more likely to be incarcerated than their nonveteran peers (Greenberg & Rosenheck, 2012). Furthermore, research has shown that increased criminal justice involvement among military veterans is partly a function of the fact that they confer a higher risk of substance abuse (Canada & Albright, 2014) and mental health disorder (Morgan et al, 2019) relative to nonveterans, both of which are comorbid (Crum-Cianflone et al, 2016)—a point substantiated most recently by a systematic review on the most pressing criminogenic risks for veterans, including antisocial behavior and substance abuse (Edwards et al, 2023). Still, other studies have suggested that veteran status corresponds with higher rates of lifetime trauma (Saxon et al, 2001) and greater risks of suicide while incarcerated (Frisman & Griffin-Fennell, 2009; Wortzel et al, 2009).…”
mentioning
confidence: 99%
“…Although the RNR model is focused on risk of future criminal justice system involvement, the empirical literature on the use of this model to examine criminogenic risk in the veteran population has largely focused on factors that are statistically associated with veterans’ self-reports of prior criminal offenses (Blonigen et al, 2016; Edwards et al, 2023). Criminal history may be used as a proxy for criminogenic risk in this population because health care systems such as the Veterans Health Administration do not typically have access to either data on recidivism risk from validated measures or official records on criminal offending.…”
mentioning
confidence: 99%
“…Criminal history may be used as a proxy for criminogenic risk in this population because health care systems such as the Veterans Health Administration do not typically have access to either data on recidivism risk from validated measures or official records on criminal offending. In this vein, systematic reviews using the lens of the RNR model have found that a history of antisocial behavior and substance use have the strongest associations with a history of criminal justice system involvement among veterans, with modest evidence for antisocial personality patterns, family/marital dysfunction, and employment problems as risk factors (Blonigen et al, 2016; Edwards et al, 2023). Few studies have examined antisocial cognitions or antisocial associates as predictors for a history of justice system involvement in veterans.…”
mentioning
confidence: 99%